Bosniak academic essay in the mirror of the poststructural theoretical turn - Spahić, Vedad (Historical Thought, 2025)
An essay writing holds a central position in the academic interpretative practices of Bosniak authors. This paper analyses that phenomenon by focusing on the work of Enes Duraković, who most completely describes the path from loyalty to this model to liberation that occurred parallel to the cataclysm of war and ethnopolitical, socio-structural and cultural shocks that marked the history of Bosnia and Herzegovina at the turn of the millennium. The shift occurs by adapting the traditions of postmodernism, post-structuralism, and postcolonialism, revealing thus if not the illusion, then certainly institutionalism of truths and their dependence on the socio-discursive order. In that sense, it is particularly interesting to observe the Bosniak academic reflection on literature within the rational choice theory.